Representation of Archaic Beliefs in Texts of Different Styles - Dinara Murzubraimova; Begimai Abdilaziz kyzy; Guljamal Aitmatova; Kyzburak Madanova; Venera Orozbaeva (Pharos Journal of Theology)
The aim of the work was to study the interaction of pre-Islamic Turkic beliefs with Islamic ideas in the texts of Kutadgu Bilig (Yusuf Balasaguni), Diwan-i Hikmat (Ahmed Yasawi), Book of Dede Korkut, and Tarikh-I-Rashidi (Mirza Muhammad Haidar Douglat). The latter work highlighted Sufi and tribal connections, which served as an important context for conceptualizing the interaction between traditional and Islamic beliefs. The research methodology was based on comparative-historical and contextual analyses, which allowed the influence of archaic beliefs and their adaptation in the Islamic value system to be identified. The results showed that each of the analysed texts represents a unique synthesis of archaic and Islamic traditions. In Kutadgu Bilig, symbolic characters representing cosmic balance and Tengrian beliefs were noted, which were organically combined with Islamic ethics. In Ahmed Yasawi’s Diwan-i Hikmat, traditional Turkic elements, images of nature, and purification rituals were reinterpreted through Sufi theology, contributing to the integration of Islam into the daily life of Turkic peoples. The Book of Dede Korkut retained the archaic motifs associated with shamanism but adapted them by introducing the Islamic concept of monotheism and moral duty. In Tarikh-I-Rashidi, Sufi and tribal ties were intertwined, reflecting the interaction of localized beliefs with broader Islamic ideas that supported stability in the political and social spheres.